The pragmatic development of Iranian English learners across proficiency levels in the performance of the requestive speech act - Najafabadi, Shahla Amooaliakbari (2013)
The present study investigated the interlanguage pragmatic knowledge of Iranian English learners at three levels of English language proficiency. The study focused on learners’ ability to perform the speech act of request in different social situations,and their performance was compared with American native speakers of English to see to what extent they approximated native speakers in performing different requestive features as direct and conventionally indirect strategies, external and internal modifications, and alerters. A Discourse Completion Task (DCT) was employed to elicit performance data from 120 participants, 90 Iranian language learners of English and 30 American native speakers of English. The DCT included 12 situations in which each situation was based on the variation of two social power and distance variables providing six different social situations. The data were categorized using an adapted version of the Cross-Cultural Speech Act Realization Project (CCSARP) classification. The study found that Iranian English learners used more direct strategies and fewer conventionally indirect strategies than native speakers, but with higher levels of proficiency the learners moved in the direction of the native speaker norms, that is,they used fewer direct strategies and more conventionally indirect strategies. It was found that Iranian English learners used more external modifications than native speakers; however, they showed development in the direction of native speakers as their proficiency level increased. Language learners used less internal modifications than native speakers; however, they showed development in the direction of the native speakers as their proficiency level increased. It was also found that language learners used more alerters compared to native speakers; however, the use of alerters used by language learners reduced by increase in language proficiency level. As a whole the study showed that with increase in language proficiency level Iranian language learners showed pragmatic development in using the requestive speech act. In addition, Iranian pragmatic competence in using requests in English approximated native speakers’ norms of use with regard to the use of conventionally indirect strategy and external modifications in higher level of language proficiency. However, they did not approximate native norms with regard to the use of direct strategy, internal modifications, and alerters.